Epidemiology and treatment of hepatocellular carcinoma in Thailand - Soonthorn Chonprasertsuk; Ratha‐Korn Vilaichone (2016)
Hepatocellular carcinoma (HCC) is the most frequent type of malignant liver tumor in Thailand. The high incidence rate of HCC reflects from chronic HBV infection in this endemic area. Some patients are asymptomatic at presentation whereas many of them presented at advanced stage of HCC with limited treatment options and grave outcome. The Barcelona Clinic Liver Cancer (BCLC) staging system and management allocation for HCC is widely accepted and used in many international guidelines including Thailand. Curative treatment is expected in early stage of HCC while palliative treatment, combination treatment and best supportive care are offered to advanced stage of HCC. The most effective strategy to prevent the development of HCC is prevention of HBV vertical transmission and treatment HBV or HCV infection. The purpose of this article is to update information of HCC in Thailand including epidemiology, diagnosis, clinical manifestation, and treatment.